Controlled Natural Language Second International Workshop, CNL 2010, Marettimo Island, Italy, September 13-15, 2010. Revised Papers - Rosner, Michael; Fuchs, Norbert E. (Lecture Notes in Artificial Intelligence,, 2012)
This book constitutes the refereed proceedings of the Second International Workshop on Controlled Natural Language, CNL 2010, held in Marettimo Island, Italy, in September 2010. The 9 revised papers presented in this volume, together with 1 tutorial, were carefully reviewed and selected from 17 initial submissions. They broadly cover the field of controlled natural language, stressing theoretical and practical aspects of CNLs, relations to other knowledge representation languages, tool support, and applications.